2009
DOI: 10.1037/a0012819
|View full text |Cite
|
Sign up to set email alerts
|

Explaining elevated social anxiety among Asian Americans: Emotional attunement and a cultural double bind.

Abstract: Previous research has documented elevated levels of social anxiety in Asian American college students when compared with their European American peers. The authors hypothesized that higher symptoms among Asians could be explained by cultural differences in attunement to the emotional states of others. Socialization within interdependent cultures may cultivate concerns about accurately perceiving other's emotional responses, yet at the same time, norms governing emotional control may limit competencies in emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
91
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 54 publications
12
91
0
Order By: Relevance
“…First, we examined the relationship between individual factors and cognitive process variables using undergraduate students as little attention has been devoted to their experiences of cognitive processes (Goto & Takeuchi 2002;Greenland & Brown 1999), particularly in an Australian context. We substantiated the findings of previous studies mostly conducted in the United States that gender is a predictor of anxiety & apprehension (Tsui, Egan & O'Reilly 1992) and nationality is a predictor of bias (Ancis, Sedlacek & Mohr 2000;Kessler, Michelson & Williams 1999;Kohatsu et al 2000;Pham & Dykstra 1994), stereotyping (Pham & Dykstra 1994) and anxiety & apprehension (Lau et al 2009;Okazaki 1997;Okazaki et al 2002). However, we found that the relationships between gender and bias, and gender and stereotyping were not statistically significant.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…First, we examined the relationship between individual factors and cognitive process variables using undergraduate students as little attention has been devoted to their experiences of cognitive processes (Goto & Takeuchi 2002;Greenland & Brown 1999), particularly in an Australian context. We substantiated the findings of previous studies mostly conducted in the United States that gender is a predictor of anxiety & apprehension (Tsui, Egan & O'Reilly 1992) and nationality is a predictor of bias (Ancis, Sedlacek & Mohr 2000;Kessler, Michelson & Williams 1999;Kohatsu et al 2000;Pham & Dykstra 1994), stereotyping (Pham & Dykstra 1994) and anxiety & apprehension (Lau et al 2009;Okazaki 1997;Okazaki et al 2002). However, we found that the relationships between gender and bias, and gender and stereotyping were not statistically significant.…”
Section: Discussionsupporting
confidence: 56%
“…Anxiety is found to be greater in intergroup than in interpersonal encounters (Gudykunst & Shapiro 1996). For instance, research has found ethnic differences in the experiences of anxiety, noting a greater level of social anxiety among Asian American students relative to European American students (Fritz, Chin & DeMarinis 2008;Lau et al 2009) or White American students (Okazaki 1997;Okazaki et al 2002). Similarly, Asians experience more anxiety than Hispanics when interacting with Caucasians (Stephan & Stephan 1989).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This indicates a high magnitude effect in the difference in prevalence rates with greater prevalence amongst European-Americans. In contrast, nonepidemiological studies 1 have demonstrated that individuals of Asian-heritage (AH), tended to report higher levels of social anxiety symptoms than did their Europeanheritage (EH) 2 counterparts (Okazaki, 1997;Hsu et al, 2012;Lau et al, 2009;Norasakkunkit and Kalick, 2009), creating an apparent discrepancy in the literature.…”
Section: Levelmentioning
confidence: 58%
“…There is evidence to suggest that the prevalence rate of social anxiety differs between European-Americans and ethnic minority groups, particularly Asian-Americans, but the findings appear to be mixed (Okazaki, 1997;Hsu, 2004;Hsu et al, 2007;2008;2012;Lau et al, 2009;Norasakkunkit and Kalick, 2002;Norasakkunkit, Kitayama, and Uchida, 2012;Lee, Okazaki, and Yoo, 2006;Abe and Zane, 1990;Gordon and Teachman, 2008;Hardin and Leong, 2005;Sue et al, 1983;. For instance, some epidemiological studies reported a greater 12-month prevalence rate for social anxiety amongst European-Americans as compared to AsianAmericans (3.01% and 2.3%, respectively; Smith et al, 2006), while others report the difference being as great as 7.3% (European-Americans: 12.6% and Asian-Americans: 5.3%; Asnaani et al, 2010).…”
Section: Levelmentioning
confidence: 99%
See 1 more Smart Citation